2021
DOI: 10.1186/s40662-020-00225-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between corneal biomechanical parameters and corneal sublayer thickness measured by Corvis ST and UHR-OCT in keratoconus and normal eyes

Abstract: Background To explore the relationship between corneal biomechanical parameters and corneal sublayer thickness using corneal visualization Scheimpflug technology (Corvis ST) and ultrahigh-resolution optical coherence tomography (UHR-OCT) in clinical and suspected keratoconus and normal eyes. Methods Cross-sectional prospective study. A total of 94 eyes of 70 participants were recruited. Twenty five eyes of 19 keratoconus patients, 52 eyes of 34 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…The human corneal stroma is mainly composed of collagen lamellae, which accounts for approximately 90% of the overall thickness of the cornea [ 17 ]. The corneal strength derives from the meshwork of the collagen lamellae, which play a crucial role in the maintenance of normal corneal functions [ 18 , 19 ]. Our previous animal study has confirmed that the surgically designed “stromal pocket” at a depth of 160 μ m from the cornea epithelium facilitates the recovery of the surgical incision of 2.5 mm without damaging the biomechanical stability of the cornea [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human corneal stroma is mainly composed of collagen lamellae, which accounts for approximately 90% of the overall thickness of the cornea [ 17 ]. The corneal strength derives from the meshwork of the collagen lamellae, which play a crucial role in the maintenance of normal corneal functions [ 18 , 19 ]. Our previous animal study has confirmed that the surgically designed “stromal pocket” at a depth of 160 μ m from the cornea epithelium facilitates the recovery of the surgical incision of 2.5 mm without damaging the biomechanical stability of the cornea [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diğer yandan, pigmenter glokom olgularında trabeküler ağın endotel hücrelerinde pigment birikiminin hücre ölümüne neden olabildiği bildirilmiştir 29 . Benzer şekilde pigmenter glokom ve pigment dispersiyon sendromlu olgularda kornea endotel hücrelerinde belirgin pleomorfizm ve polimegatizm saptandığı rapor edilmiştir 30 18 . Korneal sertliğin yaş ile artış gösterdiği bilinmektedir 31 ve SSI'nın olgularımızda yaş ile aynı yönlü bir korelasyon göstermesi beklenen bir sonuç olarak değerlendirilebilir.…”
Section: Discussionunclassified
“…AS-OCT is also useful in the pre-operative, intra-operative, and post-operative evaluations of corneal refractive surgery candidates [ 33 ]. Ultra-high-resolution OCT can effectively detect subclinical keratoconus [ 34 , 35 ], an important part of pre-operative screening for refractive surgery. High-resolution AS-OCT is useful for the measurements of corneal thickness, corneal keratometry, flap thickness or displacements after laser in situ keratomileusis (LASIK) [ 36 , 37 ].…”
Section: Oct and Octa For The Assessment Of Ocular Structures In Myopesmentioning
confidence: 99%